ANALISIS DAMPAK KEHADIRAN PASAR MODERN MALL TERHADAP PASAR TRADISIONAL DI KOTA BENGKULU - Mutmainnah, Elni; Mufriantie, Fithri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2017)
The presence of modern market in Bengkulu city indirectly affect the shopping pattern of Bengkulu city community which in turn will affect the performance of traders in traditional markets. This research is conducted to investigate the impact of modern market presence on traditional market with parameter observed including turnover amount of merchants, merchandise turnover, number of traders, number of trader hours, profit margins of traditional traders in Bengkulu city before and after the establishment of modern market. The population in this study are oil, sugar and durable goods traders and fruit traders in traditional markets, which are still actively trading before and after the establishment of modern traditional markets. Twenty fife durable good traders and 15 fruit traders are selected randomly. Data is analyzed using Paired t-test method. The results show that there are differences in turnover, opening hours, and profit margins of traditional traders in Bengkulu city before and after the establishment of modern market. Suggestion in this research is to enforce discipline and control of officer routinely to the illegal traders not to trade along the road and sidewalk.